Transcatheter aortic valve replacement for bicuspid aortic valve stenosis with first- and new-generation bioprostheses: a systematic review and meta-analysis. (25th November 2020) - Ueshima, D; Nai Fovino, L.N.F; Brener, S.J.B; Pavei, A.P; Fraccaro, C.F; Napodano, M.N; Tarantini, G.T
Abstract: Background: Subjects with bicuspid aortic valve (BAV) have been excluded from transcatheter aortic valve re- placement (TAVR) randomized trials. Methods: With this meta-analysis of observational studies we first compared TAVR outcomes of BAV vs. tricuspid aortic valve (TAV) patients, stratifying the results by device generation. Then, we looked for differences between balloon-expandable (BE) and self-expandable (SE) bioprostheses in BAV patients. Primary outcome was 30-day mortality. Secondary outcomes were 30-day stroke, moderate-severe paravalvular leakage, new pacemaker im- plantation, vascular complications and 1-year mortality. Results: Thirteen studies (11, 032 patients, 7291 TAV and 3741 BAV) and seven studies (706 patients, 367 treated with BE, 339 with SE valve) met inclusion criteria. Thirty-day (OR=1.13; 95% CI: 0.88–1.46, p=0.33) and 1-year mortality (OR=1.02; 95% CI: 0.77–1.37, p=0.87) were similar between patients receiving TAVR for BAV or TAV. Subjects treated for BAV were at higher risk of conversion to conventional surgery (OR=2.35; 95% CI: 1.30–4.23, p=0.005), implantation of a second valve (OR=2.06; 95% CI: 1.31–3.25; p=0.002), moderate/severe paravalvular leakage (PVL) (OR=1.67; 95% CI: 1.29–2.17; p=0.0001) and device failure (OR=1.26; 95% CI: 1.02–1.56; p=0.04). Rates of adverse events decreased significantly with the use of new-generation devices, but outcome differences remained consistent. BAV patients treated with BE vs. SE valves had similar 30-day and 1-year mortality, stroke and moderate-severe PVL. Balloon-expandable valves were associated with lower rates of a second valve and new pacemaker implantation but carried higher risk of annular rupture. Conclusions: BAV patients treated with TAVR had similar 30-day and 1-year mortality as well as stroke and new pacemaker implantation rates compared to TAV subjects, but carried higher risk of moderate/severe PVL, conver- sion to surgery and device failure. Event rates significantly decreased with the use of new-generation devices, but TAVR still showed better procedural results in TAV compared to BAV. Funding Acknowledgement: Type of funding source: None